Bretton Woods System: Eksistensi Hegemon Amerika Serikat Dalam Tatanan Perekonomian Global Paska Perang Dunia - Saragih, Andika Amrija (Global and Policy Journal of International Relations, 2016)
ABSTRACTThe strength of the United States in economic and military put him in the position in leadership as the most dominant actor after the outbreak of the First World War. The dominance showed in every decision and activity he participated in the political constellation and the global economy. One is through Bretton Woods System which is formed as well as the idea of the United States relating to the change and improvement of the structure of the post-war international monetary system. In the prewar period, the countries in the world more use gold as a single exchange rate system. But after the outbreak of the First World War, many countries experienced a decline in growth rates and instability in economic conditions due to the depleted gold reserves used to finance the war. The Bretton Woods System present to give enlightenment to all countries in order not to repeat the mistakes of the past which resulted in disruption of world economic structure. The system also managed to create international institutions such as the IMF, World Bank and WTO. The third institution initiated by the United States is the primary regulator in the respective proportions and play a role in promoting the liberalization of the economy. However, the Bretton Woods system did not last long because the great crisis facing the US in the 1970s led to the instability of the US domestic economic conditions that led to the collapse of the system which has been built for nearly half of the century.Keywords: United States, Bretton Woods System, liberal, economy, crisisDOI : https://doi.org/10.33005/jgp.v4i02.1921